Altruistic Economic Behaviors and Implicit Worldviews - Masao Ogaki; SunYoun Lee; Byung-Yeon Kim; Hyeog Ug Kwon; Hyoung-Seok Lim; Fumio Ohtake (European Regional Science Association (ERSA), 2014)
The main purpose of this paper is to study how individual differences in implicit worldviews regarding categories versus relationships affect altruistic behavior towards parents, children and non-family members, using the survey data of Korea, Japan and the US. Altruism and intergenerational transfers have been widely studied in economics (Fehr and Schmidt, 2006). Despite the reluctance to use a cultural factor as the determinant for the economic outcomes because of its ambiguity and difficulty of the measurement, extent literature in the field of economics has recently analyzed the possible impacts of individual beliefs and preferences on a variety of economic outcomes (Guiso et al. 2006). Since the variation is not explained by income differences, a natural candidate for explaining such variation is culture. Some researchers have found elements in explicit worldviews (or belief systems) such as confidence in worldview beliefs have statistically significant effects on intergenerational altruistic attitudes and explain substantial proportions of international differences in them (Akkemik et al. 2013; Kubota et al. 2013). Our research question is how worldviews affect altruistic economic behavior towards parents, children and non-family members. Following an approach of studying cultures in anthropology explained in Hiebert (2008), we see a worldview behind each culture. Here, a worldview consists of the explicit and implicit levels. He posits different types of logics at the implicit level of the worldviewlogic and relational logic. This difference corresponds with Nisbettfs (2003, pp. 139-147) hypothesis based on intellectual traditions in ancient Greece and ancient China is that Westerners would have a greater tendency to categorize objects than would Easterners. Nisbett cites experimental evidence for his hypothesis. It should be noted that it is not that every Westerner categorizes and every Easterner uses relationships. The difference is in distributions. More Westerners use categories than Easterners even though an individual Westerner may use relationships. We used survey data of Korea, Japan and the US that contains various measures of implicit and explicit worldviews, and individual preferences. We found that implicit worldviews as well as confidence in spiritual beliefs in explicit worldviews have statistically significant effects on some altruistic attitudes. This paper mainly differs from the previous literature in that it uses unique data that represent implicit worldviews about categories and relationships. The estimation results of this study contribute to shedding light on the effect of an individual foundational framework that is formulated at the implicit level on altruistic economic behaviors.
Keywords: D03; D64; 330; culture; implicit and explicit worldviews; categories; relationships; altruism